2020
DOI: 10.1186/s12885-020-06949-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of immune checkpoint receptor expression by circulating T cells and tumor specimens in patients receiving neo-adjuvant chemotherapy for operable breast cancer

Abstract: Background While combinations of immune checkpoint (ICP) inhibitors and neo-adjuvant chemotherapy (NAC) have begun testing in patients with breast cancer (BC), the effects of chemotherapy on ICP expression in circulating T cells and within the tumor microenvironment are still unclear. This information could help with the design of future clinical trials by permitting the selection of the most appropriate ICP inhibitors for incorporation into NAC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Recently, a clinical trial found that the induction of chemotherapy in TNBC causes a favorable tumor immunologic microenvironment and increases sensitivity to PD-1 blockade 44 . In another study by Wesolowski et al, the authors concluded that neo-ACT influences the immune microenvironment by downregulating CD4+ and upregulating CD8+ cells, which leads to a reduction in the number of TILs and CD8+ T cells in breast cancer samples 45 . These reports are consistent with our present observations, as we observed a statistically significant potential link with chemotherapy for the METABRIC cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a clinical trial found that the induction of chemotherapy in TNBC causes a favorable tumor immunologic microenvironment and increases sensitivity to PD-1 blockade 44 . In another study by Wesolowski et al, the authors concluded that neo-ACT influences the immune microenvironment by downregulating CD4+ and upregulating CD8+ cells, which leads to a reduction in the number of TILs and CD8+ T cells in breast cancer samples 45 . These reports are consistent with our present observations, as we observed a statistically significant potential link with chemotherapy for the METABRIC cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that PD-1 and PD-L1 protein expression were associated with the prognosis in different malignant tumors ( 33 35 ). However, due to significant limitations of these studies (e.g., Ahmed FS’s study ( 36 ), Wesolowski R’s study ( 37 ), and Loibl S’s study ( 38 )), research into the potential significance of PD-1 and PD-L1 protein expression in breast cancer patients treated with NACT was often considered flawed or controversial. Therefore, in light of their research and practical significance, to bridge the research gap, the present study investigated the PD-L1 protein expression in post-NACT patients’ tumor tissues and examined the relationship between the PD-L1 protein expression and patients’ treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoints (ICPs) are co-regulatory molecules controlling T cell activation and can be classified into stimulatory and inhibitory receptors. The former include CD28, CD27, ICOS, CD226, HVEM and OX40, while the latter comprise CTLA-4 (cytotoxic T lymphocyte-associated protein-4), PD1 (programmed cell death-1), TIGIT (T cell immunoreceptor with immunoglobulin and ITIM domain), VISTA (V-domain Ig suppressor of T cell activation) and LAG-3 (lymphocyte activation gene 3) ( 13 15 ). Some molecules, like BTLA and TIM-3 (T cell immunoglobulin and mucin domain 3), could exert both stimulatory as well as inhibitory activities depending on the cellular context ( 16 18 ).…”
Section: Important Features Of Immune Checkpointsmentioning
confidence: 99%